1989
DOI: 10.1139/e89-190
|View full text |Cite
|
Sign up to set email alerts
|

Latest Quaternary and Holocene paleoceanography of the eastern Baffin Island continental shelf, Canada: benthic foraminiferal evidence

Abstract: Foraminiferal zones, radiocarbon ages on shells, and corrected ages on pretreated organic sediment from four cores from the eastern Baffin Island continental shelf suggest a three-stage deglacial to postglacial history (Late Wisconsin to Holocene). The earliest sediments in the cores contain foraminiferal species (Elphidium excavatum, Cassidulina reniforme, Islandiella helenae) indicative of distal glaciomarine environments that lasted at least several thousand years. An oceanographic change about 8500 years a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 25 publications
6
53
0
Order By: Relevance
“…This type of fauna is found in ice-distal sediments in the Canadian Arctic (Osterman and Andrews, 1983;Osterman and Nelson, 1989) and is similar to that found in present assemblages of the Thule area (Phleger, 1952;Feyling-Hanssen and Funder, 1990).…”
Section: Foraminiferasupporting
confidence: 80%
“…This type of fauna is found in ice-distal sediments in the Canadian Arctic (Osterman and Andrews, 1983;Osterman and Nelson, 1989) and is similar to that found in present assemblages of the Thule area (Phleger, 1952;Feyling-Hanssen and Funder, 1990).…”
Section: Foraminiferasupporting
confidence: 80%
“…Other studies of foraminifera in high-latitude fjord and shelf areas have found a range of environmental variables influencing their distribution. Water mass characteristics are commonly identified as important variables, particularly salinity, temperature and dissolved oxygen content (e.g., Schafer and Cole, 1986;Osterman andNelson, 1989, Hunt andCorliss, 1993;Jennings and Helgadottir, 1994;Rytter and others, 2002;Husum and Hald, 2004;Jennings and others, 2004). Other important factors that have also been identified include food supply and substrate texture (Jennings and Helgadottir, 1994;Korsun and Hald, 1998;Husum and Hald, 2004;Jennings and others, 2004); glacial proximity (Nagy, 1984;Vilks and others, 1989;Korsun and Hald, 1998) and duration of sea-ice cover (Schrö der-Adams and others, 1990a, 1990b, Osterman and others, 1999.…”
Section: Discussion Factors Controlling Faunal Assemblage Zones In DImentioning
confidence: 99%
“…Water circulation and the water masses within Disko Bugt are heavily influenced by the components of the WGC entering the bay from the southwest shown in figure 2 (Andersen, 1981). Due to the relatively shallow nature of the embayment, the colder deeper water within Baffin Bay, the Baffin Bay Deep Water (Osterman and Nelson, 1989), does not penetrate Disko Bugt. Disko Bugt is also influenced by the annual formation of sea ice during December-January and melting by April-May (Andersen, 1981), and significant meltwater flux from coastal glaciers and icebergs.…”
Section: The Study Areamentioning
confidence: 99%
See 2 more Smart Citations